Determination of the absolute jet energy scale in the DO calorimeters - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1999)
The DO detector is used to study pp collisions at the 1800 and 630 GeV center-of-mass energies available at the Fermilab Tevatron. To measure jets, the detector uses a sampling calorimeter composed of uranium and liquid argon as the passive and active media, respectively, Understanding the jet energy calibration is not only crucial for precision tests of QCD, but also for the measurement of particle masses and the determination of physics backgrounds associated with new phenomena. This paper describes the energy calibration of jets observed with the DO detector at the two pp center-of-mass energies in the transverse energy and pseudorapidity range ET>8 GeV and |η|<3.